2020
DOI: 10.7717/peerj.8353
|View full text |Cite
|
Sign up to set email alerts
|

Application of problem-based learning and case-based learning integrated method in the teaching of maxillary sinus floor augmentation in implant dentistry

Abstract: Background Teaching of maxillary sinus floor augmentation (MSFA) is challenging for dental educators due to the varied sinus anatomy and high rate of complications. The method integrating problem-based learning and case-based learning (PBL-CBL method) may be more effective than the traditional teacher-centered method. The aim is to evaluate the efficacy of the PBL-CBL method in teaching MSFA. Materials & Methods Ninety-two students who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 31 publications
1
23
0
2
Order By: Relevance
“…Another study conducted among first year dental students for physiology also yielded improvement of scores following CBL sessions [12]. Likewise, CBL also led to improvement of test scores among a cohort of students in Implant Dentistry [13]. The improvement in scores in our study might be attributed to the dynamic methods of learning in CBL in Group I students compared to the conventional methods in Group II, which predominantly relied on existing theoretical knowledge and memorization of histopathological images.…”
Section: Discussionsupporting
confidence: 63%
“…Another study conducted among first year dental students for physiology also yielded improvement of scores following CBL sessions [12]. Likewise, CBL also led to improvement of test scores among a cohort of students in Implant Dentistry [13]. The improvement in scores in our study might be attributed to the dynamic methods of learning in CBL in Group I students compared to the conventional methods in Group II, which predominantly relied on existing theoretical knowledge and memorization of histopathological images.…”
Section: Discussionsupporting
confidence: 63%
“…PBL pedagogy is problem-based, student-centered and teacher-guided [29]. PBL maximizes students' autonomous learning, acquiring knowledge through a process of discussion, self-study, rediscussion and relearning [15]. Bains M demonstrated that a combination of anatomy teaching and PBL could promote learning efficiency and students' comprehensive ability [2].…”
Section: Discussionmentioning
confidence: 99%
“…CBL and PBL integrated methods have been demonstrated to be better than the traditional teaching method in the teaching of other clinical courses. Liu et al adopted CBL-PBL teaching for maxillary sinus floor augmentation, and better results were obtained in terms of academic knowledge acquisition, case analysis ability, and student satisfaction compared to the traditional teaching method [ 17 ]. Zhao et al also demonstrated that in teaching about thyroid disease, CBL and PBL integrated methods improved residents’ and medical students’ performance and enhanced their clinical skills compared to the traditional teaching method [ 19 ].…”
Section: Discussionmentioning
confidence: 99%